A rare case of broad ligament hematoma masquerading ovarian malignancy in a post-menopausal woman: a case report - Verma, Sunita; Makkar, Binni; Singh, Poonam; Singh, Netra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Spontaneous broad ligament hematomas are relatively rare in non- pregnant state. We hereby present a case report of a 73 year old post-menopausal female, who initially presented with complain of postmenopausal bleeding since 4 month. Patient had underwent a diagnostic endometrial curettage in an another hospital, prior to presenting to our institution. On imaging, she was found to have a right sided complex adenexal mass (about 5cm in size) suspicious of ovarian malignancy. Patient was taken up for exploratory laparotomy and per-operatively found to have a broad ligament hematoma, which was further confirmed on histopathological examination.